Wandering albatross, Diomedea exulans, and the flightless moth, Pringleophaga marioni, on sub-Antarctic Marion Island : a case of thermal ecosystem engineering - Haupt, Tanya Magdeleen (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.